Flapping membrane wing: a prediction towards inter-domain flight - Abas, M. F.; Aftab, Syed Mohammed Aminuddin; Mohd Rafie, Azmin Shakrine; Yusoff, Hamid; Ahmad, Kamarul Arifin (Universiti Putra Malaysia Press, 2016)
The purpose of this research is to gain initial knowledge and to predict the sustainability of an all-weather Micro-Aerial-Vehicle (MAV). The observed parameters are: the maximum coefficient of lift, CL and the changes in CL after impact, the fluctuation of CL upon entering simulated rain environment, and length of stability recovery in terms of time and flapping cycle, t and t/T, at flapping frequencies of 8, 16, and 24 Hz, at t/T = 3/8 and 7/8. At 24 Hz, the increase in peak CL value after impact of entering rain environment is 0.59. The average fluctuations in CL occurred when entering the rain environment are 410.263. The stability recovery time recorded is 0.006 seconds. Small birds (especially hummingbirds) have a very high flapping frequency that enables them to efficiently withstand external disturbances caused by nature and to instantly adapt to new environments.